I Have a Voice: Examining Augmentative and Alternative Communication Application According to Parent's Opinions - Aslı Avcıl; Ertan Görgü (Anı Publishing, 2022)
Augmentative and Alternative Communication Systems (AAC) is an important method for individuals with limited verbal communication (speech) to access communication tools and communicate accordingly. This research examines the application process of the "I Have A Voice" Program, which produces tablet and computer-assisted speech, designed to support the communication skills of individuals with limitations in the verbal communication process, according to the parents' opinions. Within the scope of the research, while describing the application process of the "I Have a Voice" program, it is also aimed to examine the possible problems related to the application and its causes. Another aim of the study is to examine the views of family members about the tablet program and the effect of the Program on family members. In this context, 3 parents who received the tablet program training constitute the research participants. The research was carried out with a case study, one of the qualitative research methods, and the data obtained were analyzed with content analysisAAC supports accessibility and equality so that those with limited verbal communication can independently participate in a social order based on speech. In addition, if these systems are to be utilized effectively, parents must be taught how to use AAC.